Особливості порушення менструальної функції у жінок із дифузним нетоксичним зобом - Литвак, О. О.; Хабрат, Б. В.; Лисенко, Б. М.; Підаєв, А. В.; Юзвенко, Т. Ю. (Clinical Endocrinology and Endocrine Surgery, 2012)
Menstrual function usually suffers in diffuse forms of goiter. With increasing of severity of thyroid disease increases the frequency of menstrual dysfunction. The most common of these were irregular menstruation, which are more common in the background of euthyroidism and opsomenorrhea, especially in women with subclinical hypothyroidism. Delay in formation of menstrual function is also more common in women with thyroid pathology.